2020
DOI: 10.1093/ehjci/ehaa946.3668
|View full text |Cite
|
Sign up to set email alerts
|

Development of matured hiPSCs-derived 3D cardiac tissue using ERR gamma agonist and mechanical stress and application for Hypertrophic Cardiomyopathy (HCM) model

Abstract: Introduction Tissue engineering using human induced pluripotent stem cells-derived cardiomyocytes (hiPSCs-CMs) is one of the potential tools to replicate human heart in vitro. Although there are many publications on 3 dimensional (3D) heart tissues (1), these tissues show fetal like phenotypes. For that reason, several maturation methods such as electrical stimulation and mechanical stress have been investigated (2, 3). However, these methods have been inadequate in differentiating fetal like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The essential role of ERRα and ERRγ in controlling cardiac metabolism and mitochondrial and contractile function has been demonstrated by early studies of genetic knockout mouse models [9][10][11][12][13] ; however, the ability to activate these processes in vivo with ERR agonists has not been demonstrated previously. Although chemical library screening has led to identification of agonists for ERRα, 17,18 ERRγ, 19,93 and ERRβ/γ, 20 no study has demonstrated the bioavailability of these compounds for in vivo use. As such, it was necessary for us to develop a novel chemical tool compound that would have in vivo exposure so that the therapeutic potential of targeting ERRs in vivo could be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential role of ERRα and ERRγ in controlling cardiac metabolism and mitochondrial and contractile function has been demonstrated by early studies of genetic knockout mouse models [9][10][11][12][13] ; however, the ability to activate these processes in vivo with ERR agonists has not been demonstrated previously. Although chemical library screening has led to identification of agonists for ERRα, 17,18 ERRγ, 19,93 and ERRβ/γ, 20 no study has demonstrated the bioavailability of these compounds for in vivo use. As such, it was necessary for us to develop a novel chemical tool compound that would have in vivo exposure so that the therapeutic potential of targeting ERRs in vivo could be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…14 Therefore, ERRs have been proposed as candidate therapeutic targets for treating HF and other metabolic diseases. 15,16 Although several ERR agonists have been developed, [17][18][19][20] no study has demonstrated their potential use for HF treatment in vivo. As such, the therapeutic potential of these critical metabolic regulators remains untested.…”
mentioning
confidence: 99%
“…While ERR-targeting therapy has been proposed for heart failure therapy, no natural ligand was identified nor synthetic agonist with favorable pharmacokinetics that can be used for in vivo studies had been developed (15, 16). Although there have been compounds identified as ERRα agonists (17, 18), ERRγ agonists (19), and ERRβ/γ agonists (20) through chemical library screening, none of them have been available for in vivo use and examined as a therapeutic agent for heart failure treatment in vivo . We believe that it was necessary to develop a chemical “tool” compound that would have in vivo exposure so that the therapeutic potential of targeting ERRs in vivo could be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ERRs have been proposed as candidate therapeutic targets for treating heart failure and other metabolic diseases (15,16). Despite several ERR agonists having been previously developed (17)(18)(19)(20), no study has demonstrated the potential utility for heart failure treatment in vivo. In this study, we report the cardiac protective effect of a recently described ERR pan-agonist SLU-PP-332 (332) and another novel structurally distinct ERR pan-agonist SLU-PP-915 (915) in pressure overload-induced heart failure.…”
Section: Introductionmentioning
confidence: 99%